The Influence Of Perceived Quality On Repurchase Intention With The Mediating Customer Satisfaction And Perceived Value Of Cosmetic Products In Jabodetabek - Purnamasari, Dita Satriana; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The increasing development of cosmetic products leads to fierce business competition. Cosmetic products are a basic necessity for women and part of a woman's lifestyle to look beautiful and confident. Almost all women depend on cosmetic products. This study aims to determine the effect of perceived quality, customer satisfaction and perceived value on repurchase intention. This research was conducted on female customers aged 17 years and over who have experience more than 2 times buying cosmetic products for at least the last 6 months in Jabodetabek. The sampling method used purposive sampling with a total sample of 95 respondents. The number of statements given to respondents was 19 statement items. The results of this study indicate a significant effect on perceived quality on customer satisfaction and perceived quality on perceived value, as well as an insignificant effect on customer satisfaction on repurchase intention, perceived value on repurchase intention and perceived quality on repurchase intention. Keywords: Perceived Quality, Customer Satisfaction, Perceived Value, Repurchase Intention